PENGARUH LATIHAN OPERAN JARAK JAUH TERHADAP KETEPATAN PASSING JARAK JAUH PADA SISWA EKSTRAKURIKULER SEPAKBOLA SMP NEGERI 38 PEKANBARU - Fajar Nuryono; Ramadi Ramadi; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The purpose of this research is to find out if there is the influence of excercise a distance of accuracy of passing distance at the extra football in junior high school 38 Pekanbaru. The design of this study uses a group of the research is wearing the approach one group pretest-posttest design , with a population team football in the junior high scholl 38 Pekanbaru, the data in this research is the whole population of 16 people. The sample in this study, using a technique the total sampling are used is a sample of saturated and that’s where all the population as a sample. The instruments used in this research is a test accuracy of passing, that aims to measure accuracy of passing distancein football. After that, the data is processed with statistics,to test normality with a lilifors test at significance level α (0.05). The hypothesis put forward is the influence of the passing a distance of accuracy of passing distance. Based on the analysis of statistical data, the data pree test Lhitung of 0,2123 data post test Lhitung of 0,1590 and Ltabel 0,220, then Lhitung < Ltabel. Based on data analysis pree-test and post-test there are differences in the numbers are rising or an increase of 2,13 . Based on t test analysis produces Ttabel >Thitung of 11,66 and 1,753, meaning Thitung> Ttabel. Thus, there is the influence of exercise a distance of accuracy of passing distance at the extra football in junior high scholl 38 Pekanbaru.Keywords : A Distance, A Accuracy Of Passing Distance.